Silk Fabric Market Segment Expansion Strategy of Kampoeng BNI Program (Case Study in Sengkang Bugis Silk Craftsman Center, Wajo District, Selatan Sulawesi) - Sari, Seli Arum; Suranto, S (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to analyze segmentation strategies, determine targeting, and determine positioning in Kampoeng BNI (Bugis Sengkang Silk Craftsmen Center). The type of research used is qualitative research with a case study design. Data collection techniques with observation, interviews and documentation. The validity of the data contained in this study uses a triangulation technique. Data analysis techniques by detailing data, presenting data, and drawing conclusions. The results of the study show that: 1) the segmentation strategy in Kampoeng BNI (Sengkang Bugis Silk Craftsmen Center) uses a geographic, demographic, psychographic, and behavioral segmentation approach. Geographical segmentation includes Makassar City, Bone Regency, Soppeng Regency and Tana Toraja. Demographic segmentation includes women aged 25 to 40 years. Psychographic segmentation targets the social class of consumers with income from the upper middle class. Behavioral segmentation is seen from the attitudes and responses of consumers who buy products at that place. 2) Targeting in Kampoeng BNI (Bugis Sengkang Silk Craftsmen Center), namely women who need references to fashion trends and use silk fabrics for everyday use. Product sales are also targeted at local communities who still use woven fabrics as everyday clothes or for traditional events. 3) The positioning in Kampoeng BNI (Bugis sengkang silk craftsman center) is the many variations of motifs with various colors provided with 2 types of fabric, namely silk and non-silk.